Efetivitas tablet Fe dalam meningkatkan kadar hemoglobin ibu hamil - Mila Syari; Rahmi Fitria; Elvina Sari Sinaga; Harahap Harahap; Yuka Oktafirnanda (Fakultas Farmasi Universitas Tjut Nyak Dhien, 2023)
Introduction: Iron deficiency is when a person has a low number of red blood cells (erythrocytes) in the blood, causing anaemia. Anaemia occurs due to a lack of haemoglobin, which means a lack of oxygen supply throughout the body. Lack of oxygen can cause the body to become weak, lethargic, and lacking energy. In pregnancy, anaemia can occur because the increase in plasma volume is greater than the increase in haemoglobin levels. Purpose: This study aims to determine the effectiveness of Fe tablets in increasing Hb levels in pregnant women at the Amaliun Health Center. Methods: This study used an analytical, quantitative method with a pre-experimental design using a one-group pre-test and post-test design. Data was collected using a questionnaire and data analysis using the T-Dependent test. The research sample consisted of 38 pregnant women. Results: The results showed that the average difference in Hb levels before and after being given Fe tablets was 1.5 gr% ± 0.57 gr%. The statistical test results showed a value of p = 0.00, which means that Fe tablets have an effect on increasing haemoglobin levels in pregnant women. Conclusion: This study concluded that Fe tablets had a significant effect with p=0.00. Therefore it is expected that the puskesmas will provide counselling and health counselling to prevent anaemia during pregnancy.